2021
DOI: 10.1108/jarhe-07-2021-0254
|View full text |Cite
|
Sign up to set email alerts
|

Staying positive among negativities: strategies employed by teachers in Sri Lankan state universities to manage their wellbeing

Abstract: PurposeTeacher wellbeing is critical given its impact on students’ experience and achievement. This qualitative study provides insights into teacher wellbeing in Sri Lankan state universities. The study occurs during the coronavirus disease (COVID-19) pandemic, where institutions are stretched for resources and teachers sought better work–life balance while working from home.Design/methodology/approachThe study uses semi-structured interviews of teachers from four state universities in Sri Lanka to discover th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
2
0
1
Order By: Relevance
“…mas megoldásokat a különböző munkáik (oktatás, kutatás, tanácsadás), valamint a magánéletük összehangolásához. A tanárok jóléte nemcsak őket érinti, hanem közvetlen hatással van a hallgatók jólétére is (Fernandez-Chung & De Zoysa, 2021). A munka nem önmagában determinálja az életminőség ezen részeit, így a család és a munka összeegyeztetése is eredeztethető az életminőség kérdéséből.…”
Section: Cikkek Tanulmányokunclassified
“…mas megoldásokat a különböző munkáik (oktatás, kutatás, tanácsadás), valamint a magánéletük összehangolásához. A tanárok jóléte nemcsak őket érinti, hanem közvetlen hatással van a hallgatók jólétére is (Fernandez-Chung & De Zoysa, 2021). A munka nem önmagában determinálja az életminőség ezen részeit, így a család és a munka összeegyeztetése is eredeztethető az életminőség kérdéséből.…”
Section: Cikkek Tanulmányokunclassified
“…Researchers have demonstrated that teacher' well-being can be defined as a combination of personal professional achievement, satisfaction, purpose and happiness; it is constructed in the process of collaboration with colleagues and students; and it is related to teachers' environment and interactions with other people in the work environment (Acton and Glasgow, 2015;Brady and Wilson, 2021;McLellan and Steward, 2015). In addition, researchers have focused on the different impact dimensions of teacher well-being, including workload, individual pressure, relationship between teacher and students, work climate, accountability, job satisfaction, selfefficacy, professional identity and so on (Brady and Wilson, 2021;Collie et al, 2015;Fernandez-Chung and De Zoysa, 2022;Yeigh et al, 2022). Diener et al (2009) identified two new measures of well-being and combined psychology and social well-being theory to create psychosocial flourishing measurements to help assess individual levels of well-being.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, researchers have focused on the different impact dimensions of teacher well-being, including workload, individual pressure, relationship between teacher and students, work climate, accountability, job satisfaction, self-efficacy, professional identity and so on (Brady and Wilson, 2021; Collie et al. , 2015; Fernandez-Chung and De Zoysa, 2022; Yeigh et al. , 2022).…”
Section: Literature Reviewmentioning
confidence: 99%